Carenage, Trinidad, B.W.I. - (:unkn) unknown (My University, 2009)
From the shoreline a structure seems to be sitting gently on the water just off the shore.
Colour; Black and White; Style: Portrait; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Cities and towns--Trinidad and Tobago--Carenage; Shorelines--Trinidad and Tobago; Coasts--Trinidad and Tobago